Image of Women in Saki´s Short Prose - Kufnerová, Nela (Univerzita Pardubice, 2012)
This bachelor thesis deals with the image of women in the short prose of hector Hugh Munro writing under the pseudonym "Saki". The critical and strongly negative portrayal of female characters in Saki's short stories is analyzed through the comparison with the Edwardian ideals and stereotypical conception of women. Also, the author's experiences influencing the portrayal are dealt with. The thesis is divided into two main parts. The theoretical part is focused on the historical background, woman idol and essential information about Saki's life and literary style is provided. The analytical part is aimed on the image of women in selected short stories in relation to other characters in the stories, such as men and children.
Zobrazení žen v Sakiho krátké próze
Keywords: Saki; Munro; edwardovská společnost; ženy; obraz; Edwardian society; women; image